즉각적 말하기와 쓰기 출력에 나타난 한국인 영어 학습자의 동사구와 명사구 오류분석 - 강혜영; 조상래; 이용은 (언어과학, 22(3), 2015)
The aim of this study is to investigate the types of verb and noun phrase errors that Korean EFL learners produce both in their spontaneous speech and in their written output. To this end, 20 participants―grouped into two proficiency levels, i.e., High Intermediate and Low Intermediate―were asked to orally describe as well as to provide written descriptions of two sets of paired pictures. They were also required to revise the transcribed version of their spontaneous speech. The results suggest as follows. (i) Subject-verb agreement errors in VP and determiner errors in NP accounted for the highest ratio in both speech and written outputs by both of the two proficiency groups. (ii) Self-revised data revealed that participants easily discovered verb agreement errors, while most of them failed to correct determiner errors. We conclude that the current errors reflect interlingual transfer to a greater extent than intralingual transfe KCI Citation Count: 7